2017
DOI: 10.1111/sms.12867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of habitual exercise on urinary liver‐type fatty acid‐binding protein levels in middle‐aged and older adults

Abstract: The purpose of this study was to examine the effect of habitual exercise on urinary liver-type fatty acid-binding protein (L-FABP), which can reflect the degree of various stresses on renal proximal tubule related to the progression of renal disease, in middle-aged and older adults. Cross-sectional and interventional approaches were used to comprehensively achieve this purpose. In the cross-sectional study, we investigated the relationship between physical activity levels and urinary L-FABP levels in 130 middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Although the reduction in renal blood flow by the high‐intensity exercise is likely to be transient, the kidney is vulnerable to hypoperfusion and hypoxia, and therefore, may be affected by renal hypoxia due to the high‐intensity exercise. While there are previous studies shown the continuous moderate‐intensity exercise may have a beneficial effect on the kidney, the influence of high‐intensity exercise on the renal conditions are still not fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Although the reduction in renal blood flow by the high‐intensity exercise is likely to be transient, the kidney is vulnerable to hypoperfusion and hypoxia, and therefore, may be affected by renal hypoxia due to the high‐intensity exercise. While there are previous studies shown the continuous moderate‐intensity exercise may have a beneficial effect on the kidney, the influence of high‐intensity exercise on the renal conditions are still not fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…There is also some evidence from literature about the role of PA on other interesting markers like CAF and urinary L-FABP [40], but further studies should be designed to confirm and fully explain these results.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a recent paper investigated the possible role of PA on renal proximal tubule stress levels through the evaluation of urinary levels of liver-type fatty acid-binding protein (L-FABP). The intent of the study was two-fold: in a cross-sectional evaluation, urinary L-FABP levels were significantly lower in those subjects with higher PA levels than in those with lower PA levels; in the interventional study, those subjects that underwent 12 weeks of aerobic training had significantly decreased levels of urinary L-FABP [40].…”
Section: Effect Of Pa On Other Biohumoral Markersmentioning
confidence: 99%
“…The results of the present study indicated a correlation between urinary markers and sarcopenia in mature rats with T2D and DKD. Our previous studies found that lower physical activity or weaker muscle strength was related to increased urinary L-FABP levels, but not urinary albumin [10], and that intervention with aerobic exercise training facilitated a reduction in increased urinary L-FABP in healthy middle-aged and older adults [11]. Furthermore, decreased muscle strength was independently associated with increased intrarenal vascular resistance [19], suggesting that sarcopenia might lead to impairments to the intrarenal vasculature.…”
Section: Discussionmentioning
confidence: 98%
“…Urinary liver-type fatty acid-binding protein (L-FABP) accurately reflects the degree of tubulointerstitial damage [7,8] and has been accepted as a tubular marker by the Ministry of Health, Labour and Welfare in Japan [9]. Moreover, a study by our group found that urinary L-FABP levels were inversely associated with exercise capacity or physical activity and that aerobic exercise training decreased urinary L-FABP levels in healthy middle-aged and older adults [10,11]. Therefore, urinary L-FABP may be useful to monitor the progression of sarcopenia.…”
Section: Introductionmentioning
confidence: 99%